Henry A. Wise papers - Wise, Henry A. (Henry Augustus), 1819-1869.
Correspondence, scrapbook of newspaper clippings, photographs, sketches, and other papers concerning Wise's books which relate chiefly to the seafaring life. Correspondents include Gustavus Vasa Fox, Matthew Fontaine Maury, and Edward Maynard.
Naval officer and author.
Forms part of: Naval Historical Foundation collection.
Keywords: Fox, Gustavus Vasa, -- 1821-1883 -- Correspondence; Maury, Matthew Fontaine, -- 1806-1873 -- Correspondence; Maynard, Edward, -- 1813-1891 -- Correspondence; Seafaring life in literature; Authors; Naval officers